2020
DOI: 10.1177/0093854820977577
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Self-Esteem, Gender, Criminal Attitudes, and Recidivism in a Youth Justice Sample

Abstract: The Risk-Need-Responsivity (RNR) model deems criminal attitudes a high-priority criminogenic target for both genders while self-esteem is considered noncriminogenic, hence low priority. In contrast, self-esteem is afforded greater priority among gender-responsive researchers, while the construct of criminal attitudes is afforded lesser priority. We examined whether self-esteem and gender moderated the relationship between criminal attitudes and recidivism among 300 justice-involved youth (200 males, 100 female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Further, scholars such as Wormith (1984) have demonstrated that when high self-esteem exists alongside criminal attitudes the probability of criminal behaviour occurring increases. In an attempt to replicate the Wormith study, Thapa et al (2021) also found that high self-esteem was related to recidivism alongside the presence of high criminal attitudes, but only among girls. Recently it has been suggested that current self-esteem measures, such as the Rosenberg Self-Esteem Scale (RSES, Rosenberg, 1965) may be erroneously detecting narcissism instead of genuinely high self-esteem (Rosenthal et al, 2020).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Further, scholars such as Wormith (1984) have demonstrated that when high self-esteem exists alongside criminal attitudes the probability of criminal behaviour occurring increases. In an attempt to replicate the Wormith study, Thapa et al (2021) also found that high self-esteem was related to recidivism alongside the presence of high criminal attitudes, but only among girls. Recently it has been suggested that current self-esteem measures, such as the Rosenberg Self-Esteem Scale (RSES, Rosenberg, 1965) may be erroneously detecting narcissism instead of genuinely high self-esteem (Rosenthal et al, 2020).…”
Section: Discussionmentioning
confidence: 95%
“…Further, it has been suggested that some self-esteem measures may be erroneously detecting related but distinctly different constructs such as narcissism (e.g., Salmivalli, 2001). The findings revealed in the Thapa et al (2021) study leave scholars questioning whether high self-esteem really is correlated with higher rates of recidivism, or whether there may be other confounding variables at play, such as narcissism. It is possible that the girls in the Thapa et al study evidenced genuinely high self-esteem.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…When implementing projects aimed at the rehabilitation and resocialization of violent offenders, it is necessary to research and analyse violence-related attitudes from the viewpoint of violent offenders that mostly are males (out of nine penitentiary institutions in Latvia, only one is for female prisoners). Assessment of criminal attitudes is one of the key components (alongside other psychological factors such as self-esteem) in programs and interventions aimed at reducing recidivism (Thapa, Brown, Skilling, 2020). To provide this assessment, valid measurement methods are needed.…”
Section: Introductionmentioning
confidence: 99%